Photoreduction of Shewanella oneidensis Extracellular Cytochromes by Organic Chromophores and Dye‐Sensitized TiO2. (8th November 2016) - Ainsworth, Emma V.; Lockwood, Colin W. J.; White, Gaye F.; Hwang, Ee Taek; Sakai, Tsubasa; Gross, Manuela A.; Richardson, David J.; Clarke, Thomas A.; Jeuken, Lars J. C.; Reisner, Erwin; Butt, Julea N.
Abstract: The transfer of photoenergized electrons from extracellular photosensitizers across a bacterial cell envelope to drive intracellular chemical transformations represents an attractive way to harness nature's catalytic machinery for solar‐assisted chemical synthesis. In Shewanella oneidensis MR‐1 (MR‐1), trans‐outer‐membrane electron transfer is performed by the extracellular cytochromes MtrC and OmcA acting together with the outer‐membrane‐spanning porin⋅ cytochrome complex (MtrAB). Here we demonstrate photoreduction of solutions of MtrC, OmcA, and the MtrCAB complex by soluble photosensitizers: namely, eosin Y, fluorescein, proflavine, flavin, and adenine dinucleotide, as well as by riboflavin and flavin mononucleotide, two compounds secreted by MR‐1. We show photoreduction of MtrC and OmcA adsorbed on Ru II ‐dye‐sensitized TiO2 nanoparticles and that these protein‐coated particles perform photocatalytic reduction of solutions of MtrC, OmcA, and MtrCAB. These findings provide a framework for informed development of strategies for using the outer‐membrane‐associated cytochromes of MR‐1 for solar‐driven microbial synthesis in natural and engineered bacteria. Abstract : Pump priming : Outer‐membrane cytochromes provide conduits for electron exchange between bacteria and their environment. Photoreduction of these cytochromes has been achieved. This research paves the way to light‐driven microbial synthesis by use of extracellular photosensitizers to harness nature's versatile catalytic machinery.